Proses Komunikasi antara Guru dan Siswa di SMA Gema 45 Surabaya - Qurrata A’yun, Ariza; Zuhro, Fatimatus; Madaniah, Aulia (Jurnal Ilmu Komunikasi, 2023)
This research aims to analyze the communication process between teachers and students at SMA Gema 45 Surabaya and understand how this interaction influences the learning process. This research uses qualitative research methods with an educational case study approach. The research results show that effective communication between teachers and students at SMA Gema 45 Surabaya is supported by several factors, including openness, message clarity, and constructive feedback. This research identified that teachers who are able to communicate lesson material clearly and are responsive to student needs tend to create a more productive learning environment, Ineffective communication can hinder students' understanding and reduce learning motivation. This research also found that non-verbal communication, such as body language and facial expressions, plays an important role in interactions between teachers and students. Good interpersonal communication skills of teachers contribute to the creation of positive relationships with students, which has an impact on improving learning outcomes.